Slope—sedimentary source rock-type helium enrichment model: a case study of Shenmu Gas Field, Ordos Basin - Zhengang DING; Chenglin LIU; Liyong FAN; Rui KANG; Jianfa CHEN; Haidong WANG; Sijie HONG; Aslam Khan MUHAMMAD (Shiyou shiyan dizhi)
The Ordos Basin is rich in helium resources, with high helium and helium-rich natural gas fields discovered in areas such as the Yimeng Uplift and the southern Yishan Slope. The enrichment of helium in these gas fields is often closely related to the development of faults. However, the structural background within the basin is complex. To study the characteristics and controlling factors of helium enrichment under different geological backgrounds within the basin, an analysis of natural gas composition was conducted in the northeastern Yishan Slope of the Ordos Basin. Combining basic geological data of the study area and previous research findings, the helium distribution characteristics and geological influencing factors in the Upper Paleozoic of the Shenmu Gas Field in the Ordos Basin were explored. The results showed that the helium content in the Upper Paleozoic of the Shenmu Gas Field ranged from 0.017% to 0.116%, with an average content of 0.05%, meeting the standard of a helium-containing gas field. The helium content showed a spatial distribution pattern of "low in the west and high in the east", with helium content exceeding 0.1% in some eastern areas. There was a significant positive correlation between helium and nitrogen content, indicating a possible inherent connection between the genesis and dissolution-exsolution mechanisms of helium and nitrogen in natural gas reservoirs. The enrichment of helium in the Shenmu Gas Field was influenced by various geological factors: (1) The widely distributed coal-measure source rocks in the Upper Paleozoic provided ample helium; (2) Crustal uplift and tectonic inversion controlled the migration direction of helium and promoted the exsolution and accumulation of dissolved helium; (3) An appropriate amount of carrier gas aided in helium enrichment. Based on the tectonic conditions of the study area and the geological factors controlling helium accumulation, a new helium enrichment model was proposed, the slope-sedimentary source rock-type helium-rich natural gas enrichment model, providing theoretical support for helium exploration and development.